Characterization of 298 Patients with Lung Cancer HarboringMETExon 14 Skipping Alterations. Issue 9 (September 2016) - Schrock, Alexa B.; Frampton, Garrett M.; Suh, James; Chalmers, Zachary R.; Rosenzweig, Mark; Erlich, Rachel L.; Halmos, Balazs; Goldman, Jonathan; Forde, Patrick; Leuenberger, Kurt; Peled, Nir; Kalemkerian, Gregory P.; et al.
ABSTRACT : Background: : The hepatocyte growth factor receptor gene ( MET ) exon 14 skipping ( METex14 ) has recently been described a potential driver alteration in lung cancer targetable by mesenchymal‐to‐epithelial transition factor (MET) tyrosine kinase inhibitors (TKIs). Methods: : Well‐validated hybrid capture–based comprehensive genomic profiling was performed at the request of individual treating physicians. Results: : Of 11, 205 lung cancers profiled by comprehensive genomic profiling, 298 (2.7%) carcinomas harbored alterations predicted to cause METex14, including adenosquamous (8.2%), sarcomatoid (7.7%), histologic subtype not otherwise specified (3.0%), adenocarcinoma (2.9%), squamous cell (2.1%), large cell (0.8%), and SCLC (0.2%). Acinar features were present in 24% of the METex14 samples. Six cases (2%) harbored MET Y1003X mutations affecting binding of the MET‐negative regulator, E3 ubiquitin protein ligase. The median age of all patients with METex14 was 73 years (range 43–95) and 60% were female. Concurrent, murine double minute gene ( MDM2 ) amplification, cyclin‐dependent kinase 4 gene ( CDK4 ) amplification, and EGFR amplification were observed in 35%, 21%, and 6.4% of patients with METex14, respectively. KRAS mutation was observed in 3% of cases. Concurrent MET amplification ( MET amp) (median copy number 10) was identified in 15% of METex14 samples. Significant differences in tumor mutational burden and type of the METex14 alterations were observed between the MET amp and non‐ MET amp samples. Response to MET TKI was observed in both in patients with MET amp and in patients without MET amp METex14 . Conclusion: : Diverse targetable METex14 alterations were identified in patients with NSCLC across age groups, including elderly patients, and in all major NSCLC histologic subtypes with an overall frequency of 2.7%. These findings support the use of hybrid capture–based molecular profiling across NSCLC subtypes to identify patients who will potentially benefit from MET TKIs.